The effect of different weight loss strategies to treat non-alcoholic fatty liver disease focusing on fibroblast growth factor 21 - Power Guerra, Nicole; Leyens, Katharina; Müller, Luisa; Brauer, David; Janowitz, Deborah; Schlick, Samin; Pilz, Kristin; Grabe, Hans J.; Vollmar, Brigitte; Kuhla, Angela (Frontiers in Nutrition, 2022)
Objective: Obesity, often associated with nonalcoholic fatty liver disease (NAFLD), is characterized by an imbalance between energy expenditure and food intake, which is also reflected by a desensitization of fibroblast growth factor 21 (FGF21). FGF21 is strongly influenced, among others, by TNFα, which is known to be upregulated in obesity-induced inflammation. Successful long-term treatments of NAFLD might be dietary modification, exercise or fasting. Methods: Whether succeeded NAFLD recovery is linked with improved FGF21 sensitivity and finally reverted FGF21 resistance was the focus of the present study. For this purpose, mice received a high-fat diet (HFD) for 6 months to establish obesity. Afterwards, mice were subjected to three different weight loss interventions, namely dietary change to low-fat diet (LFD), treadmill training and/or time-restricted feeding for additional 6 months, whereas one group remained on HFD. Results: In addition to the expected decrease in NAFLD activity with dietary change, this was also observed in the HFD group with additional time-restricted feeding. There was also an associated decrease in hepatic TNFα and FGF21 expression and an increase in ß-klotho expression, demonstrated mainly by principal component analysis. Pearson correlation analysis shows that independent of any intervention TNFα expression decreased with improved NAFLD recovery. This was accompanied with higher FGF21 sensitivity, as expressed by an increase in β-klotho and FGFR1c expression and concomitantly decreased FGF21 levels. Conclusions: In summary, we conclude that successful NAFLD therapy is associated with a reversion of TNFα-triggered FGF21 resistant state or desensitization.